2013
DOI: 10.1007/s11010-013-1640-8
|View full text |Cite
|
Sign up to set email alerts
|

Epistatic interaction of Arg72Pro TP53 and −710 C/T VEGFR1 polymorphisms in breast cancer: predisposition and survival

Abstract: The tumour-suppressor gene TP53 has been associated with the angiogenic pathway by a TP53 response element sequence of the VEGFR1 promoter. Within that sequence, the polymorphism -710 C/T VEGFR1, which confers variable transcriptional activation by TP53, has been identified. Our group found an association between this polymorphism and breast cancer (BC) risk. We decided to investigate a possible epistatic interaction between this polymorphism and others located at gene TP53. We chose four polymorphisms (Ex4 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
2
4
1
Order By: Relevance
“…Interestingly, [ 49 ] observed on a relatively large set of Finnish samples that patients carrying the homozygous variant CC genotype of rs1042522 had significantly poorer survival than BC patients with other genotypes. A similar pattern of association was also observed in the study of Toyama et al (2007) on Japanese BC women, in the one on a Chinese population [ 24 ] and more recently in the work of [ 26 ] on a Spanish group of BC. Interestingly, patients with rs1042522 GC genotype were at lower risk of relapse or metastasis, as well as those with the less frequent haplotype A 1 -C-C-G.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Interestingly, [ 49 ] observed on a relatively large set of Finnish samples that patients carrying the homozygous variant CC genotype of rs1042522 had significantly poorer survival than BC patients with other genotypes. A similar pattern of association was also observed in the study of Toyama et al (2007) on Japanese BC women, in the one on a Chinese population [ 24 ] and more recently in the work of [ 26 ] on a Spanish group of BC. Interestingly, patients with rs1042522 GC genotype were at lower risk of relapse or metastasis, as well as those with the less frequent haplotype A 1 -C-C-G.…”
Section: Discussionsupporting
confidence: 84%
“…Instead, a recent meta-analysis on rs17878362 (PIN3, Ins11951_11966, allele A2 carries the 16-bp insertion within intron 3) has found an increased risk of BC in A 2 A 2 carriers [ 22 ]. Previous studies have suggested rs1042522 as a prognostic marker for BC [ 23 26 ]. On the contrary, the role of TP53 haplotypes has not yet been fully investigated for BC susceptibility and its clinical outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were documented in Caucasians (Mavridou et al, 1998), Turkish (Akkiprik et al, 2009) and Spanish (Rodrigues et al, 2013) breast cancer patients. In contrast to our results, association of r.13494g>a polymorphism with the risk of developing breast (Peller et al, 1995), ovarian (Wang-Gohrke et al, 1999) and colon (Peller et al, 1995) cancer has been reported.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, RP genotype has been reported to be associated with increased breast cancer risk in Iranian population (Boroujeni et al, 2013). Association of Pro allele with increased risk of breast cancer has been reported in Swedish (Sjalander et al, 1996), American (Weston et al, 1997), German (Wang-Gohrke et al, 1998, Russian (Suspitsin et al, 2003), Japanese (Huang et al, 2003;Noma et al, 2004), Slovakian (Franekova et al, 2007), Turkish (Akkiprik et al, 2009), Iranian (Kazemi et al, 2009), Kashmiri (Sayeed et al, 2010), Arabic (Alawadi et al, 2011), Austrian (Proestling et al, 2012) and Spanish (Rodrigues et al, 2013) population. Individuals with PP genotype had an increased risk of developing a cancer over their lifetimes compared to individuals with RR genotype (van Heemst et al, 2005).…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, Tp53 Pro allele has been found to be associated with BC risk in North Indian [23], Austrian [22], Bangladeshi [28], Iranian [21], Turkish [30], Spanish [32], Swedish [26], American [34], German [33], Russian [36], Japanese [25], and Slovakian [35] populations. In addition, a meta-analysis performed by Gonçalves et al [31], involving 25629 BC cases and 26.633 controls from 41 studies, reported an increased BC risk due to TP53 Pro allele dominant model, but not among Asian subgroup where the risk was associated with TP53 Arg allele and the Arg dominant model.…”
Section: Discussionmentioning
confidence: 99%